2019
DOI: 10.1016/j.gca.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the unique achondrite Northwest Africa 6704: Constraints from petrology, chemistry and Re–Os, O and Ti isotope systematics

Abstract: Northwest Africa (NWA) 6704 is a unique achondrite characterized by a near-chondritic major element composition with a remarkably intact igneous texture. To investigate the origin of this unique achondrite, we have conducted a combined petrologic, chemical, and 187 Re-187 Os, O, and Ti isotopic study. The meteorite consists of orthopyroxene megacrysts (En 55-57 Wo 3-4 Fs 40-42 ; Fe/Mn = 1.4) up to 1.7 cm in length with finer interstices of olivine (Fa 50-53 ; Fe/Mn = 1.1-2.1), chromite (Cr# ~ 0.94), awaruite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 154 publications
(193 reference statements)
4
46
0
Order By: Relevance
“…By contrast, some achondrites that crystallized within ~1 Myr of NWA 7325 (e.g., NWA 6704; Hibiya et al. ) originated from parent bodies that underwent relatively limited planetary processes. Therefore, it must be concluded that contemporary planetary bodies underwent variable degrees of differentiation in the early solar system.…”
Section: Implications For Early Planetary Processesmentioning
confidence: 99%
“…By contrast, some achondrites that crystallized within ~1 Myr of NWA 7325 (e.g., NWA 6704; Hibiya et al. ) originated from parent bodies that underwent relatively limited planetary processes. Therefore, it must be concluded that contemporary planetary bodies underwent variable degrees of differentiation in the early solar system.…”
Section: Implications For Early Planetary Processesmentioning
confidence: 99%
“…, Hibiya et al . ), the NWA 6704 ungrouped achondrite yielded markedly positive values of ε 54 Cr and ε 50 Ti. The isotope compositions are within the range of carbonaceous chondrites (Figure ), in striking contrast to those of other primitive achondrites, such as acapulcoite and lodranite, which are similar to non‐carbonaceous meteorites (Larsen et al .…”
Section: Resultsmentioning
confidence: 85%
“…The latter has a chondritic (primitive) bulk composition and comprises mostly orthopyroxene megacrysts (Hibiya et al . ). For the Juvinas and NWA 6704 specimens, pieces of bulk samples were disaggregated in an agate mortar.…”
Section: Methodsmentioning
confidence: 97%
“…The texture, geochemistry, and mineralogy of the NWA 6704 meteorite group were initially interpreted as an igneous cumulate melt origin Jambon et al 2012;Warren et al 2013;Archer 2017). More recently, Hibiya et al (2019) concluded that the NWA 6704 meteorites formed from a superheated melt, which either favors an impact-melt origin or a not fully differentiated asteroid process. Based on Pb-Pb dating, the crystallization age of NWA 6704 was determined to be 4.56280±0.00046 Ga (Iizuka et al 2013) .…”
Section: Introductionmentioning
confidence: 99%
“…Such rapid accretion may, however, be at odds with expectations of slower accretion at larger heliocentric distances. Near-chondritic values represented in the highly siderophile elements and rare-earth elements also suggest that the parental melt or protolith material that the NWA 6704 meteorite group is derived from did not experience differentiation processes (Hibiya et al 2019). This would include separation of silicate, metal, and sulfide material, and perhaps rapid cooling after being extremely heated (as demonstrated by the volatile depletions) with no time allowance for magmatic differentiation to proceed (Hibiya et al 2019).…”
Section: Introductionmentioning
confidence: 99%